Philanthropy, entrepreneurship and transnational exchange: women's campaigns for employment in Berlin and London, 1859-1900 - Richmond, Sarah Louise (2011)
This thesis focuses on the 'moral panic' provoked by single, 'redundant' middle-class women in the nineteenth century and extends current research by exploring the debate in Europe from both a comparative and transnational perspective. Both pitied and pilloried, unmarried women were deemed to be 'surplus' women and two institutions were established in Berlin and London to provide them with vocational training and employment: the Lette-Verein and the Society for Promoting the Employment of Women respectively. This thesis contends that a comparative study is vital in understanding their work and that hitherto undiscovered transnational lines of communication between them shaped their aims, achievements and development.